Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/cbin.10961
|View full text |Cite
|
Sign up to set email alerts
|

The CNPY2 enhances epithelial‐mesenchymal transition via activating the AKT/GSK3β pathway in non‐small cell lung cancer

Abstract: The survival of non-small cell lung cancer (NSCLC) is poor due to high metastasis, and the indispensable step of metastasis includes epithelial-mesenchymal transition (EMT). In the study, by analyzing the dataset of the Cancer Genome Atlas (TCGA), we found that the expression of Canopy homolog 2 (CNPY2) is increased both in adenocarcinoma and squamous cell carcinoma, which is further confirmed in NSCLC tissues. Not only that, there is a negative correlation between CNPY2 and E-cadherin expression at mRNA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…We next analyzed the roles of miR-30a-3p and CNPY2 in regulating EMT in EKVX cells. Consistent with a previous report (25), our data showed that CNPY2 knockdown led to downregulation of N-cadherin protein and upregulation of E-cadherin expression (Fig. 4A), suggesting EMT suppression.…”
Section: Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…We next analyzed the roles of miR-30a-3p and CNPY2 in regulating EMT in EKVX cells. Consistent with a previous report (25), our data showed that CNPY2 knockdown led to downregulation of N-cadherin protein and upregulation of E-cadherin expression (Fig. 4A), suggesting EMT suppression.…”
Section: Variablessupporting
confidence: 93%
“…miR-30a-3p targets CNPY2 in regulating EMT-associated proteins in vitro. CNPY2 was reported to enhance epithelial-mesenchymal transition (EMT), an essential step of metastasis in NSCLC (25). We next analyzed the roles of miR-30a-3p and CNPY2 in regulating EMT in EKVX cells.…”
Section: Variablesmentioning
confidence: 99%
“…Serine/threonine kinase (AKT) is closely related to the occurrence of EMT (15,16), and is involved in many biological and pathological processes, such as angiogenesis, invasion, and metastasis (17). In addition, the glycogen synthase kinase (GSK)-3β pathway is the classical downstream pathway of AKT, and often participates in the development of EMT with AKT (18). Furthermore, Snail expression can be regulated via the AKT/GSK-3β signaling pathway (19), and activation of this pathway may promote EMT in hepatoma cells (20) and ovarian clear cell carcinoma cells (21).…”
Section: Introductionmentioning
confidence: 99%
“…M3 muscarinic acetylcholine receptors regulated EMT, perineural invasion, and metastasis in cholangiocarcinoma via the Akt pathway . Canopy homologue 2 promoted EMT via activating the Akt/GSK3 pathway in non–small‐cell lung cancer . The Akt signaling pathway mediated cigarette‐induced EMT in lung cancer .…”
Section: Small Molecules Against Emtmentioning
confidence: 87%